Η μουσική παράδοση της Ινέπολης - Δραγούμης Μάρκος Φ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2009)
This article is about the folk music of Inepolis (now Inebolu) before the expulsion of its Christian community in 1922. Among its population almost 30% were Greeks established there since time immemorial. They had their own schools, churches and local festivals. The most important yearly festival was the Feast of the Dormition of the Virgin Mary on August 15. The instruments accompanying the dances were the violin or the lyra (known in the Middle Ages as rebec) and a small frame drum with jingles. The dances were the same as those danced in the other Greek communities of Western Asia Minor such as the Syrtos and the Zeibekikos. There were about a dozen tunes with a particular local flavour used for the singing of a much larger number of folk ballads in Greek, as well as a few characteristic instrumental round dances. This material was recorded in 1931, 1984 and 1989, and is presented here in 14 musical examples transcribed by the present writer.